Acute Angle Closure Glaucoma OD dengan Subluksasi Lensa Anterior OD: Laporan Kasus dan Tinjauan Pustaka - Khamila, Shifa; Prinandita , Kantika (Syntax Corporation, 2025)
Acute angle closure glaucoma (AACG) is an emergency ophthalmological condition that can cause permanent blindness if not treated quickly. The accompanying lens subluxation can worsen the condition by increasing the risk of pupil blockade and increased intraocular pressure. Report the case of a 49-year-old man with AACG accompanied by anterior lens subluxation and discuss appropriate diagnostic and management approaches. The 49-year-old male patient came with complaints of sudden blurred right eye since 2 weeks accompanied by red eyes, nausea, and vomiting. Ophthalmological examination showed vision OD 3/60, positive conjunctival and ciliary injections, superficial front eye chambers, pupil mydriasis with negative light reflex, and subluxation of the lens to the anterior. Intraocular pressure 12.3 mmHg. The patient was diagnosed with acute angle closure glaucoma OD with subluxation of the anterior lens of OD and was given mediamento therapy. AACG with lens subluxation requires immediate treatment to prevent permanent damage to the optic nerve. A combination of medicated therapy and a surgical intervention plan is necessary to achieve optimal intraocular pressure control.